Sediment migrations drive the dynamic of macrobenthic ecosystems in subtidal sandy bedforms. (October 2021) - Robert, Alexandre Elie; Quillien, Nolwenn; Bacha, Mahmoud; Caulle, Clémence; Nexer, Maëlle; Parent, Briz; Garlan, Thierry; Desroy, Nicolas
Abstract: A traditional taxonomic approach coupled to a biological traits analysis was conducted in order to provide a new insight into macrobenthic communities associated with subtidal sandy environments. Results suggest that the macro-scale distribution of benthic communities is mainly driven by the migration rate of bedforms (sandbank, barchan dune and transversal dune) which changes the sediment grain size and reduces macrobenthic diversity. A classic scheme of species/traits succession was also observed from less to more physically disturbed areas. Finally, the high frequency of migration events homogenized macrobenthic communities between the troughs to the crest of bedforms. As bedforms areas are targeted for the commissioning of offshore windfarms the information provided by the present paper will be particularly useful to implement the environmental impact assessment required for such activities at sea. Highlights: Macrobenthic communities vary with the kind of bedforms because of the discrepancy in the intensity of sediment movements; Massive recruitment by juveniles change the structural diversity in spring but not the macrobenthic ecosystem functioning; Frequent sediment movements homogenize the macrobenthic communities between the troughs to the crest of bedforms.